Care mobilities and associated contexts of hospital-based informal caregiving in Nigeria: Towards an explanatory framework. - Kudus Oluwatoyin Adebayo; Oluwaseyi Dolapo Somefun; Mofeyisara Omobowale; Rukayat Usman (PLoS ONE)
Hospital-based informal caregiving in Nigeria is shaped by care mobilities and contextual factors such as policy contradictions and normative care philosophies. This study explores how these factors influence caregiving practices in a Nigerian tertiary health facility. Using a qualitative approach, data were gathered through interviews and observations, involving 75 participants, including 36 in-depth interviews with caregivers and inpatients, and 39 key informant interviews with staff like nurses, doctors, security guards, and ad-hoc caregivers. Findings showed that many informal caregivers traveled long distances to assist hospitalized relatives, often "hanging around" the hospital and engaging in micro-mobilities, such as running errands. Geographical distance, policy contradictions, and the financial costs of hospitalization significantly affected caregiving dynamics. Care mobilities caregivers moving within the hospital environment emerged as a critical aspect of the caregiving process. Understanding these mobilities and how they intersect with contextual factors is essential to improving caregiving experiences. The study highlights the need for policies that support informal caregivers and enhance patient outcomes, especially in terms of reducing the burdens caregivers face due to long travel distances, hospital policies, and financial challenges.